THE REFUND OF STATE FINANCIAL LOSSES DUE TO CRIMINAL ACTS OF CORRUPTION THROUGH AUDIT AGENCY AUDIT INVESTIGATION - Kristiawanto, Kristiawanto (UNISSULA, 2024)
The aim of this research is to analyze the concept of returning state financial losses resulting from criminal acts of corruption based on Audit Board of the Republic of Indonesia audits and to analyze the form of follow-up to recommendations from Financial Audit Agency audit results regarding elements of state losses resulting from criminal acts of corruption. This research is normative research. The approach method used in this research is a statutory approach. The results of this research are the role of the Financial Audit Agency terms of returning state financial losses, the Audit Board of the Republic of Indonesia has the authority to make demands for compensation from parties proven to have committed unlawful acts which resulted in state financial losses through criminal law instruments, through civil law instruments or through administrative legal instruments. The Financial Audit Agency as the holder of audit power has the right to supervise the management of state finances and provide recommendations on audit results to the House of Representatives, Regional Representative Council and Regional People's Representative Assembly for political follow-up as a supervisory function and provide recommendations to law enforcers in the event of indications of criminal acts